Do migrant students affect local students' academic achievements in urban China?. (April 2018) - Wang, Haining; Cheng, Zhiming; Smyth, Russell
Highlights: We examine if migrant students affect local students' academic achievement in China. We find migrant students have positive effect on local students' Chinese scores. We find considerable evidence of heterogeneity in the effects of migrant students. Abstract: We examine the educational spillover effects of migrant students on local students' academic achievement in public middle schools in urban China. The identification of peer effects relies on idiosyncratic variation in the proportion of migrant students across classes within schools. We find that the proportion of migrant students in each class has a small, and positive, effect on local students' test scores in Chinese, but has no significant effect on math and English test scores. We also find considerable evidence of heterogeneity in the effects of the proportion of students in the class on local students' test scores across subsamples. Local students toward the bottom of the achievement distribution, local students enrolled in small classes and local students enrolled in lower-ranked schools benefit most in terms of test scores from having a higher proportion of migrant students in their class. Our findings have important policy implications for the debate in China about the inclusion of migrant students in urban schools, and for the assignment of educational resources across schools.